CLINICAL AND FUNCTIONAL FEATURES OF ACUTE PNEUMONIA IN YOUNG CHILDREN (World Bulletin of Public Health, 2025)
The article presents the clinical and functional characteristics of acute pneumonia in young children, emphasizing its pathogenesis, diagnostic features, and course of the disease. Acute pneumonia remains one of the most common respiratory infections in early childhood, often leading to severe complications if not diagnosed and treated promptly. The study analyzes clinical manifestations such as fever, cough, respiratory distress, and auscultatory findings, as well as functional parameters including oxygen saturation and respiratory rate. The importance of early identification of severe forms, rational use of antibiotics, and monitoring of respiratory function is highlighted. The findings indicate that timely and adequate management of acute pneumonia in young children significantly reduces morbidity and mortality rates and improves long-term respiratory outcomes.